Preparation of a coated Ti anode for producing acidic electrolyzed oxidizing water. (March 2016) - Tang, Wenwei; Li, Yanfei; Li, Weihao; Chen, Xuejin; Zeng, Xinping
Abstract: Coated Ti anodes have been prepared for producing acidic electrolyzed oxidizing water (AEOW). To improve the performance of anodes, the influence factors (sintering temperature, heat treatment time and dip-coating times) were systematically explored. The results show that the optimum sterilizing effect of AEOW is obtained in the case of sintering at 450 °C for 1 h with as many dip-coatings as possible. The sintering temperature is a critical factor. A lower temperature leads to better reaction selectivity, whereas a higher temperature results in a longer lifetime. A short heat treatment time leads to inadequate coating oxidation, a long heat treatment time prolongs the lifetime but results in high SEC. Increasing the number of dip-coatings could enhance the coating-substrate adhesion, thus extending the anode lifetime. The electrode prepared by optimization could replace the platinized Ti anode to produce AEOW. AEOW could be used as an effective disinfectant for eliminating Escherichia coli and Staphylococcus aureus . The sterilization ability is based on the combined effect of active chlorine concentration (ACC), low pH and high oxidation–reduction potential (ORP). Highlights: Higher temperature conduces to longer lifetime but cracks appear and grains grow up. Long heating time increases lifetime but makes Ru evolution and energy wasting. More dip-coatings improve oxidation, coating-substrate adhesion and lifetime. The optimum process is at 450 °C for 1 h with as many dip-coatings as possible. AEOW could be used as an effective disinfectant for Escherichia coli and Staphylococcus aureus.